Survey Tentang Kebijakan Pemerintah Terhadap Jarak Sekolah dengan Rumah Menurut Prespektif Orang Tua - Rayani, Ernida (Jurusan Pendidikan Luar Biasa Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2020)
The school is a formal institution to gain knowledge, the school plays an important role in achieving the goals of national education Every parent would want their children to go to a favorite school, proper school. Even though the school is far from where they live. environment close to children. According to (Verdiyani, 2016) strategic location and proximity to schools are the main factors parents in choosing schools. In accordance with government policies related to the zoning system this applies to children with special needs. Where children with special needs can attend school in accordance with their residence. This study aims to find out how parents' views are related to government policies, where students should study near their homes. Keywords: School, distance, school